To solve the expression (-2)×(1/5)÷(2/3)×(-5/6)÷(3/4), we will follow the order of operations, which is parentheses, multiplication/division (from left to right), and addition/subtraction (from left to right).
First, let's simplify the multiplication:
(-2)×(1/5) = -2/5
Next, let's simplify the divisions:
-2/5 ÷ 2/3 = -2/5 × 3/2 (Note that dividing by a fraction is the same as multiplying by its reciprocal.)
We can simplify this:
-2/5 × 3/2 = (-2 × 3) / (5 × 2) = -6/10 = -3/5
Finally, let's simplify the last division:
-3/5 ÷ 3/4 = -3/5 × 4/3 (Again, dividing by a fraction is the same as multiplying by its reciprocal.)
We can simplify this expression:
-3/5 × 4/3 = (-3 × 4) / (5 × 3) = -12/15 = -4/5
So, the final simplified result is -4/5.
Use the properties of operations and rules for multiplying and dividing to solve: (−2)×(1/5)÷(2/3)×(−5/6)÷(3/4)
2 answers
wrong